Innate immunity in rickettsial infections - Londoño, Andrés F.; Scorpio, Diana G.; Dumler, J. Stephen (Frontiers in Cellular and Infection Microbiology, 2023)
Rickettsial agents are a diverse group of alpha-proteobacteria within the order Rickettsiales, which possesses two families with human pathogens, Rickettsiaceae and Anaplasmataceae. These obligate intracellular bacteria are most frequently transmitted by arthropod vectors, a first step in the pathogens’ avoidance of host cell defenses. Considerable study of the immune responses to infection and those that result in protective immunity have been conducted. Less study has focused on the initial events and mechanism by which these bacteria avoid the innate immune responses of the hosts to survive within and propagate from host cells. By evaluating the major mechanisms of evading innate immunity, a range of similarities among these bacteria become apparent, including mechanisms to escape initial destruction in phagolysosomes of professional phagocytes, those that dampen the responses of innate immune cells or subvert signaling and recognition pathways related to apoptosis, autophagy, proinflammatory responses, and mechanisms by which these microbes attach to and enter cells or those molecules that trigger the host responses. To illustrate these principles, this review will focus on two common rickettsial agents that occur globally, Rickettsia species and Anaplasma phagocytophilum.